Lithium aluminosilicate glass ceramic product with high-quartz mixed crystal as main crystal phase and production method and application of lithium aluminosilicate glass ceramic product
By using high quartz mixed crystals and cheap mineral lithium raw materials in transparent glass ceramic products, combined with appropriate amounts of clarifiers and other ingredients, the problem of difficulty in achieving low coloring, high brightness and low scattering in the prior art is solved, and economically feasible and environmentally friendly production performance is achieved.
Patent Information
- Application Number
- CN202411970098.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-02
- Filing Date
- 2021-06-30
- Publication Date
- 2025-04-08
AI Technical Summary
The existing transparent glass ceramic products are difficult to achieve low coloring, high brightness and low scattering during the production process, and are economically feasible and environmentally friendly in production performance.
By using high quartz mixed crystals as the main crystal phase, transparent colorless lithium aluminosilicate glass ceramic products, and in production, it is preferred to use cheap mineral lithium raw materials, combined with an appropriate amount of clarifier and other ingredients, the component ratio is controlled to achieve low chrominance, high brightness and low scattering.
It realizes the low color, high brightness and low scattering performance of transparent glass ceramic products, while reducing production costs, improving production efficiency, and being environmentally friendly.
Smart Images

Figure BDA0005219313380000031 
Figure BDA0005219313380000071 
Figure BDA0005219313380000081
Abstract
Description
This application is a divisional application of patent application 202110733707.3 filed on June 30, 2021. Technical Field
[0001] The invention relates to a glass ceramic product consisting of a transparent, colorless lithium aluminum silicate glass ceramic having high quartz mixed crystals as the main crystal phase according to the preamble of claim 1.
[0002] The invention also relates to a method for producing the product and its use. Background Art
[0003] Products made of LAS glass ceramics are widely used due to their excellent material properties, such as low expansion coefficient and high stability to temperature and thermal cycle changes, high strength, chemical stability and transparency. Usually, the thermal expansion characteristics are adjusted so that the material has a very low expansion in its use temperature range, usually -1.5·10 -6 / K<α 20 / 700 <+1.5·10 -6 / K. Requirements for high temperature use include that the glass ceramics maintain the required properties (e.g. thermal expansion, transmission, thermal stability) during their service life. Regarding thermal stability, the shrinkage (compression) of the glass ceramics, although small, is a key parameter at high temperatures. Since the glass ceramics in use are usually heated in an uneven manner, stresses accumulate in the product over time due to local different shrinkage degrees.
[0004] Widespread applications of LAS glass ceramic products are fire protection glass, cookers, transparent oven viewing windows, oven viewing and as cooking surfaces. In the case of use as cooking surfaces, the transparent glass ceramic plates are colored with coloring oxides or provided with an opaque, usually colored coating on the bottom side to prevent visibility of technical components and to provide a color impression. Openings in the bottom side coating enable the installation of colored and white displays, usually light-emitting diodes or screens.
[0005] Transmission and scattering are important properties for the appearance and optical performance of glass-ceramics.
[0006] The present invention relates to a class of transparent and colorless glass-ceramics, in the production of which no coloring compounds are added.
[0007] The ideal characteristics of transparent colorless glass ceramics are high transparency, i.e. high brightness and low coloration. Both mean low absorption, since absorption bands both reduce brightness and increase coloration, depending on their position in the visible spectrum. Therefore, the brightness of such glass ceramics at a thickness of 4 mm is typically greater than 80%.
[0008] In the literature, brightness is also called transmittance or overall transmission.
[0009] However, due to the nucleating agent TiO 2 and (if present) SnO 2 Due to the presence of coloring impurities such as Co, Cr, Mn, Ni and V ions and especially iron impurities present in industrial batches of raw materials, the transparent and colorless glass ceramics have some color.
[0010] Iron in ionic form as Fe 2+ or Fe 3+ And in particular by including TiO 2 The color is imparted by the coloring complex of (components required for nucleation). The brownish yellow natural color of transparent glass ceramics is largely based on electronic transitions in the coloring complex, which absorbs in the short-wave region of visible light. The most common absorbing coloring complex is the formation of adjacent Fe and Ti ions, between which electronic charge transfer processes occur. Sn / Ti complexes also lead to the natural color. The formation of these coloring complexes occurs in particular during the ceramicization of glass ceramics.
[0011] In order to reduce the concentration of the coloring complex, it is advantageous to shorten the nucleation and crystallization times. On the other hand, shortening the nucleation time leads to increased light scattering, while shortening the crystallization time leads to inhomogeneities in the product.
[0012] The transparent glass-ceramics currently available on the market represent a compromise between economic feasibility and the requirements for coloration. 2 O 3 The content is usually 150ppm. Due to the cost of low iron raw materials, higher Fe 2 O 3 The content is also economically advantageous.
[0013] To ensure sufficient nucleation, a minimum content of TiO is required. 2 Nucleating agent, because the nucleating agent can be replaced by the nucleating agent ZrO 2 and SnO 2 Instead, it has disadvantages only in melting and forming.
[0014] Another basic feature of LAS glass ceramics is scattering, which is determined by the size of crystal, birefringence and the difference between the refractive index of crystal and residual glass. Enough nucleation doses and enough nucleation times during ceramicization realize the high density of nuclei, and its effect is that the high quartz mixed crystals of growth are lower than the wavelength range of visible light with respect to size. Usually, the average crystallite size of high quartz mixed crystals is in the scope of 20nm to 50nm. For the scattering of hope, as known from the article " Nanophase Glass-Ceramics (volume 82, the 1st phase, pages 5-16, 1999, author Beall and Pickney) of Journal of the American Ceramic Society, the required condition for the high transparency of LAS glass ceramics is also the low birefringence of crystal and the good matching of the refractive index of crystal and residual glass phase.
[0015] The refractive index of the residual glass phase is adjusted by its composition and the cooling rate during ceramization.
[0016] In the case of only low scattering, the transparency is not distorted and the display is clear and clearly visible.
[0017] Therefore, even for economically viable production, absorption and scattering are optical phenomena that must be controlled.
[0018] Brightness or transmittance is described by the lightness value Y according to the CIE standard color system or by the L* value in the CIELAB color system. The German implementation of the international CIE standard is specified in DIN 5033. The CIELAB color model is standardized in DIN EN ISO 11664-4 "Colorimetry - Part 4: CIE 1976 L*a*b* color space".
[0019] In the case of glass ceramics, it is customary to quote the chromaticity c* as a measure of color in the CIELAB color system with the coordinates L*, a*, b*, calculated according to:
[0020] The coordinates of the CIELAB color system can be calculated in a known manner from the color coordinates and the brightness Y of the CIE color system.The c* value of the sample is determined by spectrophotometric measurement in transmission with the parameters of the selected standard illuminant and observer angle.
[0021] In the context of the present invention, the spectrophotometric measurements required for this purpose are carried out on polished samples in the spectral range of 380 to 780 nm. From the spectral values measured in the range represented by visible light, the transmittance of the current thickness is calculated by selecting a standard light source and an observer angle.
[0022] The scattering of glass-ceramics is determined by measuring the haze. According to ASTM D1003-13, haze is the percentage of transmitted light that deviates more than 2.5° from the mean of the incident beam.
[0023] The industrial-scale production of transparent glass ceramics is carried out in several stages. First, a crystallizable starting glass from a mixture of ceramic chips and powdered batch raw materials is melted and refined. The glass melt reaches temperatures of 1550° C. to a maximum of 1750° C., typically up to 1700° C. In some cases, high-temperature refining at temperatures above 1750° C., typically around 1900° C., is also used.
[0024] The batch raw materials of transparent, colorless and crystallizable LAS glass are mainly composed of oxides, hydroxides, carbonates and nitrates.
[0025] As the batch melts, various very different reactions that lead to glass formation occur. A description of these reactions can be found in the book "Allgemeine Technologie des Glases, Grundlagen des Schmelzens und der Formgebung" (Dr. HASchaeffer, Erlangen, September 1985). As the temperature increases, these reactions can generally be divided into: -Dehydration - Solid-state reactions in the region of grain contact (e.g. formation of silicates) -Forming carbonate melts that enclose quartz grains - Bubbles (H 2 O、CO 2 、NO x , O 2 、N 2 、SO 2 ) decomposition reaction - Formation of silicate melt.
[0026] Subsequently, the remaining ingredients of the batch are dissolved in the silicate melt.
[0027] These reaction steps are also carried out in the case of conventional raw material mixtures of batches of crystallizable starting glasses for (LAS) glass ceramics. The main components here are usually quartz sand or quartz powder as SiO 2 The source of glass components, aluminum oxide or aluminum hydroxide as Al 2 O 3 Source of ingredients, lithium carbonate as Li 2 By selecting these raw materials, less than 200 ppm and even less than 150 ppm Fe O can be provided in the glass at an acceptable cost. 2 O3 The key factor is the low impurity content of the colored iron. The main factor is the melting of the main Li 2 O and SiO 2 The remaining crystalline raw materials, such as alumina, quartz and zircon, begin to dissolve in the first liquid lithium-rich silicate phase.
[0028] Due to their high melting temperatures, these raw materials are also the last batch raw materials to be dissolved in the glass melt. They are the raw materials that determine the melting time and temperature and the energy required. In the case of high tank production, there is a risk that batch materials remain in the glass.
[0029] In the glass industry, it is well known that the use of lithium-containing minerals such as eucryptite, spodumene or petalite in bulk glass production has advantages over lithium carbonate (Haigh et al., The Lithium Minerals Industry, Glass, December 1989) because they provide a soluble source of silicon oxide compared to slightly soluble quartz. The reference states that these mineral raw materials also introduce Al 2 O 3 Composition. Cost advantages over lithium carbonate are described. Mineral lithium raw materials are obtained and processed by conventional mining methods, while lithium carbonate must be obtained from minerals by chemical reactions or from lithium-bearing salt deposits by dissolution and crystallization. Table 5 of the publication illustrates the impurities. Fe in various petalite and spodumene raw materials 2 O 3 The content is between 300 and 1000 ppm or more. In contrast, the table shows that the Fe 2 O 3 The content does not exceed 40ppm.
[0030] The advantages of mineral lithium raw materials over lithium carbonate in terms of melting, production efficiency and cost are also described in the publication "Lithium Minerals Review 2002" (Glass, 2002). However, the disadvantage of high iron content leading to coloration is pointed out.
[0031] Thus, similar to the addition of ceramic chips, the use of mineral lithium raw materials instead of lithium carbonate improves the melting of the batch raw materials, reduces the formation of sparingly soluble quartz or alumina residues, and enables faster homogenization of the glass. The overall result is a desired advantage in terms of tank production and / or energy requirements. However, if low coloration is desired in the case of transparent LAS glass ceramics, a solution must be found for the use of these raw materials with a high iron content.
[0032] In the subsequent fining process step, due to the density difference, the gas bubbles are driven upward in the glass melt by their static buoyancy and then escape into the open space. However, this operation takes a considerable amount of time and does not support the fining measures, making the production method more expensive due to the long waiting time and the resulting low tank production.
[0033] Arsenic oxide and antimony oxide are technically and economically proven fining agents for transparent glass-ceramics with regard to good bubble quality at conventional fining temperatures of 1550 to 1700°C. An increasingly popular environmentally friendly alternative to arsenic oxide and antimony oxide is the fining agent SnO 2 , alone or with one or more clarifying additives, such as halides (F, Cl, Br), CeO 2 、MnO 2 , Fe 2 O 3 , sulfur compound combination.
[0034] In general, the process steps of melting and fining the batch ingredients are particularly important to obtain a crystallizable glass with the desired homogeneity and bubble quality. For economically viable production, a high can yield with the required bubble quality is essential. The energy required to produce a certain amount of acceptable glass and reduce the greenhouse gas CO 2 emissions into the atmosphere is an important indicator for economically viable production. This target corresponds to European Directive 406 / 2009EG of the European Parliament and of the Council of 23 April 2009 on the reduction of greenhouse gases. It should be noted here that, due to its high cost, lithium carbonate also has the 2 Key drawbacks of the source.
[0035] After melting and fining, the glass is usually hot formed by casting, pressing, rolling or floating. Many applications require glass ceramics in plate form, such as sheet form. Rolling and floating processes are used to produce sheets. In order to produce these LAS glasses economically, low melting temperatures and low processing temperatures V are required in hot forming operations. A In addition, the glass must not show any devitrification during the forming process, meaning that no larger crystals larger than about 5 μm can be formed, since they would reduce the strength or be visually apparent in the glass-ceramic article. A (Viscosity 10 4dPas), it is necessary to ensure that the upper devitrification temperature of the melt is close to and preferably below the processing temperature to avoid the formation of larger crystals. In the case of forming by rolling, the critical area is the contact of the glass melt with the precious metal mold (usually made of Pt / Rh alloy) before the glass is formed by rolling and cooled. In the case of float, it is the contact of the glass with the nozzle lip and the contact of the front area of the float bath with liquid Sn, where the glass has a higher crystal growth rate.
[0036] The crystallizable LAS glass is transformed into a glass ceramic by controlled crystallization (ceramicization) during a subsequent heat treatment. This ceramicization is carried out in a two-stage heat treatment process, in which the nucleation reaction at a temperature of 680 to 800 ° C begins and the ZrO2-containing quartz crystals are formed. 2 / TiO 2 The seeds of the mixed crystal composition. High quartz mixed crystals grow on these nuclei at high temperatures. At the maximum production temperature of about 900 ° C, the microstructure of the glass ceramic is homogenized and the optical, physical and chemical properties are adjusted. Short ceramization times are advantageous for economically viable production.
[0037] Further transformation to keatite mixed crystals occurs as the temperature increases in the temperature range of about 950 to 1250° C. This transformation increases the thermal expansion coefficient of the glass-ceramic, and further crystal growth and associated light scattering results in a transition from a transparent appearance to a translucent to opaque appearance.
[0038] The names of the crystalline phases used in the literature are "β-quartz" or "β-eucryptite" as synonyms for high-quartz mixed crystals and "β-spodumene" as synonyms for hydrothermal quartz mixed crystals.
[0039] Current developments in transparent LAS glass-ceramics typically target low Fe content of 100 to 200 ppm. 2 O 3 The content optimizes coloration. This is done by using lithium carbonate as batch material.
[0040] Document EP 1837312 A1 describes the addition of 0.01 to 0.4 wt. % Nd 2 O 3 Physical decolorization of transparent glass ceramics with high quartz mixed crystals as the main crystal phase. The basis of the physical decolorization principle is that the existing absorption bands are neutralized by the complementary absorption bands of the decolorizing agent. This naturally leads to stronger light absorption, thereby reducing the brightness. In order to achieve favorable manufacturing conditions, i.e. low melting and low forming temperatures, the example glass in the document contains a high content of MgO (viscosity-reducing component) of 0.58 wt % to 1.2 wt %, which is not conducive to low coloring. The document does not provide the use of mineral raw materials such as petalite or spodumene as Li 2Any hint on the origin of the O component. 2 O 3 The content indicates that lithium carbonate was used.
[0041] Avoid TiO 2 (WO 2008 / 065167 A1) or limit TiO 2 The attempts of (WO 2008 / 065166 A1) have not yet led to industrial implementation, and TiO 2 It is a nucleating agent that partially causes the coloring complex in glass ceramics. The required substitute ZrO 2 and / or SnO 2 A higher content of nucleating agent leads to disadvantages in melting and forming, such as higher melting and forming temperatures, and leads to insufficient devitrification stability during forming. These documents do not disclose the use of mineral raw materials such as petalite or spodumene as Li 2 O Any indication of the origin of the ingredient.
[0042] Document WO 2019 / 049785 A1 describes the use of ZrO 2 The coloring is optimized by using high purity raw materials and thus reducing the content of coloring impurities such as Fe, V, Cr, rare earths and actinides. The disclosed 120 ppm Fe 2 O 3 The content indicates the use of lithium carbonate.
[0043] Document WO 2007 / 139068 A1 describes transparent or opaque white LAS glass ceramics that can accommodate large amounts of recycled material as ceramic fragments in the melt. The recycled material is decorated with inorganic pigments to introduce its components (oxides of Fe, Ni, Cr, Co and Mn) into the LAS glass ceramic. Depending on the respective decoration used for the recycled material, the content of 50 to 500 ppm of Fe 2 O 3 , 5 to 100 ppm CoO + Cr 2 O 3 +NiO+MnO, 0 to 70ppm CoO+NiO. By selecting TiO 2 , ZnO and MgO components, which can reduce the subsequent coloring of glass ceramics. This document does not provide the use of mineral raw materials such as petalite or spodumene as Li 2 The authors do not provide any hint as to the origin of the O component, but rather suggest the use of lithium carbonate, since low Fe content of 100 or 200 ppm is also disclosed in the examples. 2 O 3 Content. Except for 100ppm Fe 2 O 3With the exception of Sample 2, the samples have very strong color, with chromaticity c* values greater than 9 for the 4 mm thick sample. This is evident from the reported color coordinates a* and b*.
[0044] Document WO 2018 / 211216 A1 describes a method for producing LAS glass-ceramic products, wherein the natural raw material petalite is used as a batch raw material and Li 2 O source. Reduce the use of Al 2 O 3 and SiO 2 The amount of slightly soluble raw materials in the ingredients improves melting and clarification. The disadvantage is that Fe 2 O 3 The limit of pure petalite quality is not more than 200 ppm. Such low iron petalite quality, if available at all, is only available to a limited extent and at a higher price. The document does not mention the Fe content of glass ceramic products 2 O 3 Since Fe impurities are mainly introduced through natural raw material petalite, it can be considered that the Fe content of glass-ceramic products is 2 O 3 The content is less than 200ppm.
[0045] Therefore, in the development of transparent LAS glass-ceramic products, it is necessary to coordinate all requirements for glass and glass-ceramic, such as cheap raw materials, favorable and environmentally friendly production performance without compromising the product quality of the glass-ceramic products, such as especially color, brightness and low scattering, and shorter ceramicization time. Summary of the invention
[0046] The object of the present invention is to provide a transparent lithium aluminum silicate glass ceramic product. - it can be produced from cheap raw materials, - have favorable production properties for economically viable and environmentally friendly production, - it contains high quartz mixed crystals as the main crystalline phase, - Transparent glass-ceramic articles with low coloration, high brightness and low scattering and short ceramizing times are targeted.
[0047] This object is achieved by a transparent lithium aluminosilicate glass ceramic article having the features of claim 1 .
[0048] Another object of the present invention is to provide a method for producing a glass ceramic article and the use thereof. These objects are achieved by the other independent claims.
[0049] The transparent, colorless lithium aluminosilicate glass ceramic product according to the present invention having high quartz mixed crystals as the main crystal phase substantially comprises the following components (weight % based on oxides): and comprising at least one clarifier selected from As 2 O 3 and / or SnO 2 The content of the group is 2% by weight, wherein the chromaticity c* of the glass-ceramic product with a thickness of 4 mm measured at 2° with a D65 standard light source is greater than 3 to 7.
[0050] Li 2 O, Al 2 O 3 and SiO 2
[0051] Li oxide within specified limits 2 O、Al 2 O 3 and SiO 2 It is or becomes a necessary component of the high quartz mixed crystal phase in transparent glass-ceramic products.
[0052] For glass ceramic products, Li 2 The O content is at least 3% by weight and less than 4.5% by weight. A minimum content is required in order to achieve the desired low thermal expansion of glass ceramics with high quartz mixed crystals as the main crystalline phase. With regard to the desired low chromaticity c* of the glass ceramic product, a content above 4.5% by weight is disadvantageous. 2 The O content is preferably less than 4.3 wt %, more preferably less than 4.1 wt %, particularly preferably less than 4 wt %. The minimum content is preferably 3.2 wt %, more preferably 3.4 wt %. A particularly preferred range is 3.2 wt % to less than 4 wt %. In order to introduce Li 2 O, compared with conventional lithium carbonate, priority is given to cheap mineral raw materials such as spodumene and / or petalite and / or eucryptite. These mineral raw materials also introduce some major Al 2 O 3 and SiO 2 Element.
[0053] Al 2 O 3 The content is 19-24% by weight. Contents above 24% by weight are disadvantageous because of the tendency of mullite to devitrify during the forming process. It has also been found that in the case of short ceramizing times, scattering increases with higher contents. Therefore, less than 23% by weight is preferred. The minimum content is 19% by weight because Al 2 O 3 A low color c* is advantageous for glass ceramics. 2 O 3The minimum content is preferably at least 20% by weight.
[0054] The main SiO 2 The content of the component should be at least 62% by weight, because this is advantageous for the desired properties of the glass ceramic product, such as low thermal expansion and chemical stability. In addition, scattering is reduced in the case of a short ceramicization time. A particularly advantageous minimum content is 64% by weight. SiO 2 The content of SiO should not exceed 70% by weight because this component increases the processing temperature and melting temperature of the glass. 2 The content is preferably not more than 68% by weight.
[0055] Nucleating agent TiO 2 、ZrO 2
[0056] As an effective nucleating agent, TiO 2 The component is essential for the transparency of the glass ceramic and good production performance. Therefore, the minimum content is greater than 1.6% by weight. This minimum content enables a high nucleation rate, so that even in the case of a shorter ceramicization time, a core that promotes a low average grain size can be fully formed. Therefore, even in the case of a short ceramicization time, a glass ceramic without visually disruptive scattering can be obtained.
[0057] However, due to the formation of Fe / Ti coloring complexes, higher TiO 2 Therefore, TiO 2 The content should not exceed 2.8% by weight. 2 The content is 1.8 wt%. This minimum content is beneficial to reduce the ceramicization time and avoid scattering. TiO is particularly preferred. 2 The content is greater than 2% by weight.
[0058] In order to limit the coloring effect, preferably no more than 2.6 wt.% TiO is present. 2 .
[0059] Another nucleating agent that comes to mind is ZrO 2 .ZrO 2 The content is 1 wt% to less than 2.5 wt%. ZrO 2 The content is preferably limited to less than 2.2 wt. %, more preferably less than 2 wt. %, because higher contents deteriorate the melting properties of the batch in glass production and can cause devitrification during the forming process by forming Zr-containing crystals. 2 A higher content of nucleating agent is therefore advantageous for providing a glass-ceramic article with a low chromaticity c*. 2 The content is preferably 1.6% by weight.
[0060] MgO
[0061] Another key component for realizing the required property of glass ceramics is MgO content.MgO composition is both the composition of mixed crystal and the composition of residual glass phase, and therefore has a great influence on many properties.This composition reduces the melting and processing temperature of glass, and therefore promotes economically feasible production.MgO content should be 0.01 wt % to less than 0.5 wt %.MgO content is at least 0.01 wt %, preferably at least 0.05 wt %, more preferably at least 0.1 wt %, particularly preferably at least 0.15 wt %.In transparent glass ceramics with high quartz mixed crystal as main crystalline phase, MgO causes particularly unfavorable colored aggravation and brightness reduction.This is owing to the formation that promotes absorptive Fe / Ti coloring complex.
[0062] The MgO content should be less than 0.5% by weight, preferably at most 0.4% by weight, more preferably at most 0.35% by weight. The requirements for low coloration (chromaticity c*) of the glass-ceramic product and low processing temperature of the crystallizable glass can be reconciled particularly effectively with a MgO value in the preferred range of 0.05% by weight to 0.4% by weight.
[0063] Na 2 OwaK 2 O
[0064] Alkali Na 2 O and K 2 O reduces the melting temperature and processing temperature in glass forming. Used for ZrO 2 and SiO 2 The melting of the slightly soluble raw materials is accelerated. The content of both must be limited to no more than 1.5% by weight. Too high a content is disadvantageous because it promotes coloring by enhancing the formation of Fe / Ti coloring complexes and has an adverse effect on the time / temperature durability of the glass-ceramic product.
[0065] Na 2 The O content may be 0% by weight. It is preferably greater than 0% by weight; more preferably, the glass contains at least 0.05% by weight, particularly preferably at least 0.1% by weight of Na 2 The maximum content is preferably 1.5% by weight, more preferably 1% by weight, in particular 0.9% by weight. 2 The O content is preferably 0.1% to 1% by weight.
[0066] K 2 The O content may be 0% by weight. It is preferably greater than 0% by weight; more preferably, the glass contains at least 0.05% by weight, particularly preferably at least 0.1% by weight of K. 2The maximum content is preferably 1.5% by weight, more preferably 1% by weight, in particular 0.9% by weight. 2 The O content is preferably 0.1% to 1% by weight.
[0067] In a preferred embodiment, 0.2 wt%≤Na 2 O+K 2 O≤1.5 wt% Alkali Na 2 O+K 2 The total amount of O is more preferably not more than 1.2% by weight, particularly preferably less than 1% by weight. 2 O 3 The content has a stronger effect on coloring. In order to further improve the solubility and reduce the processing temperature, the alkali Na 2 O+K 2 The total amount of O is more preferably at least 0.3% by weight, particularly preferably more than 0.4% by weight.
[0068] More preferably, 0.4 wt% < Na 2 O+K 2 O<1 wt%.
[0069] Alkaline Earth
[0070] In order to reduce the processing temperature V in the production of glass ceramic products A And improve the devitrification stability of glass, it has been found that the CaO component is advantageous. However, in the case of short ceramicization time, it causes coloring and scattering to increase. CaO exists with a content of no more than 1.5 weight %, preferably no more than 0.8 weight %. The upper limit of CaO content is more preferably less than 0.6 weight %, to minimize scattering in the case of short ceramicization time. CaO content can be 0 weight %. Preferably, CaO is a component of crystallizable glass and glass ceramics. Therefore, its content is preferably greater than 0 weight %, more preferably ≥ 0.05 weight %, further preferably at least 0.1 weight %, particularly preferably at least 0.2 weight %. Preferred range is 0.05 weight % to 0.8 weight %.
[0071] The BaO content is preferably at most 3 wt.-%, and the SrO content is preferably at most 1.5 wt.-%. The BaO content is preferably at most 2 wt.-%, and the SrO content is preferably at most 1 wt.-%. The BaO content may be 0 wt.-%; it is preferably more than 0 wt.-%, more preferably at least 0.2 wt.-%.
[0072] The preferred range of BaO is 0.2 wt% to 2 wt%.
[0073] The SrO content can be 0% by weight. It is preferably greater than 0% by weight, in particular ≥ 0.02% by weight.
[0074] The preferred range of SrO is 0.02 wt% to 1 wt%.
[0075] In order to adjust the refractive index of the residual glass phase and match it with the high quartz mixed crystal, it is advantageous for the crystallizable glass and the glass ceramic products produced therefrom to contain CaO and / or SrO. In this case, the sum of the alkaline earth metal oxides CaO and SrO is preferably at least 0.05 wt. %, more preferably at least 0.1 wt. %, particularly preferably at least 0.2 wt. %. It is at most 1.2 wt. %, more preferably at most 1 wt. %, particularly preferably at most 0.8 wt. %, otherwise the scattering will increase again. The glass ceramic contains these components with specified limits as residual glass components. For low devitrification tendency and low scattering, CaO and SrO are advantageous as components of the residual glass phase.
[0076] Particularly advantageously, 0.1 wt. %≤CaO+SrO≤1 wt. %.
[0077] ZnO
[0078] The ZnO component helps to reduce the melting and processing temperature of the glass and reduce scattering in the case of a short ceramicization time. ZnO is incorporated into the mixed crystal phase and a part of it is also retained in the residual glass phase. 2 O component is quite in a way that this component causes the thermal expansion of glass ceramic products to be reduced. About scattering, advantageously, ZnO reduces the anisotropy of high quartz mixed crystal. This means that the difference between the a-axis and the c-axis of the crystal is reduced. Obviously, this reduces the birefringence of the crystal. Due to the increased devitrification tendency and the formation of unwanted crystalline phases, such as zinc spinel, the ZnO content is limited to a value of no more than 3 wt %. It is preferred that the ZnO content is no more than 2.5 wt %, more preferably no more than 2.0 wt %. The ZnO content can be 0 wt % or preferably greater than 0 wt %. It is preferred that the minimum content is 0.1 wt %, more preferably 0.5 wt %, and particularly preferably more than 1 wt %. The ZnO content should preferably be 0.1 wt % to 2.5 wt %.
[0079] P 2 O 5
[0080] The additive helps to improve the melting point and devitrification stability. A higher content is not conducive to the chemical stability, especially the acid stability, of the glass-ceramic product. The crystallizable glass and the glass-ceramic product produced therefrom should contain less than 4% by weight of P. 2 O 5 .P 2 O 5The content may be 0 wt% or preferably > 0 wt%. The preferred lower limit is 0.01 wt%, more preferably 0.02 wt%. The preferred upper limit is 2 wt% of P 2 O 5 , more preferably less than 1.3 wt %, particularly preferably less than 1 wt %.
[0081] The preferred range is 0.01 wt. % to <1.3 wt. %.
[0082] Fe 2 O 3
[0083] With regard to coloration and brightness, the compositions according to the invention tolerate higher contents of Fe 2 O 3 , because the formation of Fe / Ti coloring complexes is reduced. This means greater flexibility in batch raw materials and, in particular, the above-mentioned advantages of mineral lithium raw materials over lithium carbonate in terms of melting, production efficiency and cost can be utilized. Since mineral lithium raw materials contain a higher content of Al in dissolved form 2 O 3 and SiO 2 , thus reducing the proportion of sparingly soluble quartz and alumina in the batch. Melting and homogenization of the glass are accelerated, leading to advantages in terms of tank yield and / or energy requirements. In the case of these mineral raw materials, CO is not converted into molten metal as in the decomposition of lithium carbonate. 2 Introduced into the environment.
[0084] Relatively high Fe 2 O 3 The content is advantageous because it promotes the clarification of the glass. In the case of melting in fossil heated pots, Fe 2+ The content plays a crucial role in regulating the infrared absorption of the glass melt. The minimum content creates good absorption conditions for the heat radiation of the burners of the tank superstructure. This results in a good heat input to increase the temperature of the glass melt. The infrared absorption of the glass melt should not be too high, so that the tank bottom is not too cold and the glass melt is heated with sufficient uniformity over the entire depth. This is possible through a content of at least 0.025% by weight to a maximum of 0.065% by weight according to the invention.
[0085] Fe in crystallizable glasses and glass-ceramic products produced therefrom 2 O 3 The content should be at least 0.025% by weight. The minimum content is preferably 0.03% by weight, preferably 0.032% by weight, preferably 0.035% by weight, more preferably 0.038% by weight, particularly preferably 0.04% by weight. On the other hand, the concentration of the Fe / Ti coloring complex in the glass ceramic also varies with Fe. 2 O 3The coloring (chromaticity c*) increases due to absorption, while the brightness Y decreases. Therefore, the crystallizable glass and the glass-ceramic products produced therefrom should contain at most 0.065 wt. %, more preferably at most 0.055 wt. %, particularly preferably at most 0.05 wt. % Fe. 2 O 3 .
[0086] Fe 2 O 3 The preferred range is 0.03 wt% to 0.055 wt%.
[0087] MnO 2
[0088] To achieve greater flexibility in batch feedstock, the composition should contain MnO 2 Depending on their geological origin, mineral lithium raw materials may contain, inter alia, significant amounts of MnO 2 impurities. Therefore, this component is incorporated into the composition in an amount of 0.002% to 0.05% by weight. The composition according to the invention tolerates these amounts in terms of coloration and brightness. This is attributed to the MnO 2 Increased Fe 3+ Relative to Fe 2+ ratio, thus increasing the formation of Fe / Ti coloring complexes, which is attributed to the adjacent Fe 2+ Ti 4+ cation.
[0089] Addition of MnO 2 This is also advantageous because it aids in refining the glass melt.
[0090] The minimum content is preferably 0.005 wt %, more preferably 0.008 wt %, further preferably more than 0.01 wt %, particularly preferably 0.012 wt %. On the other hand, the coloring effect inherent in the glass ceramic also increases with the addition of MnO. 2 Due to absorption, the coloring (chromaticity c*) increases, while the brightness Y decreases. Therefore, the crystallizable glass and the glass-ceramic products produced therefrom should contain at most 0.05 wt. %, preferably at most 0.03 wt. %, more preferably at most 0.025 wt. % MnO 2 .
[0091] MnO 2 The preferred range is greater than 0.01 wt % to 0.03 wt %.
[0092] B 2 O 3 , PbO and fluorine
[0093] Add up to 1 wt% B 2 O 3The melting properties and devitrification stability are also improved, but this is disadvantageous in terms of the time / temperature durability of the glass ceramic. The same is true for the addition of fluorine. Both components have in common that they reduce the stability of the high quartz mixed crystals (the main crystalline phase that is essential for transparent glass ceramics) and promote the transformation into the hot quartz mixed crystal phase. The glass ceramic preferably contains less than 0.5% by weight, particularly preferably less than 0.2% by weight of B. 2 O 3 For technical purposes, it is more preferred that the glass-ceramic article does not contain B 2 O 3 , which means that the content is lower than 1000 ppm, preferably lower than 500 ppm, more preferably lower than 100 ppm.
[0094] The preferred upper limit for the fluorine content is 0.5 wt %. The content should more preferably be less than 0.2 wt %, more preferably less than 0.1 wt %, more preferably less than 500 ppm, particularly preferably less than 200 ppm.
[0095] Adding PbO improves the melting and devitrification stability, but is beneficial for the time / temperature durability of the glass ceramic product, but is undesirable for an environmentally friendly composition. The content should be preferably less than 0.1 wt%, more preferably less than 100 ppm. More preferably, no PbO is added, and only a content of typically less than 5 ppm from impurities is present.
[0096] Coloring compounds
[0097] The glass preferably does not contain any other coloring compounds, such as Ce, Cr, Ni, Cu, V, Mo, W and / or S, which cause yellow, orange, brown or red colors, except for unavoidable impurities, due to reduced brightness and increased coloration. The content is preferably less than 20 ppm and comes from impurities in the batch of raw materials used. Therefore, a total maximum content of 0.1% by weight is still acceptable.
[0098] Coloring oxide Cr has been found 2 O 3 and NiO are particularly detrimental to coloring. In order to comply with the chromaticity c* of up to 7 according to the invention, Cr 2 O 3 The total amount of +NiO is preferably less than 7 ppm, more preferably less than 5 ppm. The unit ppm is used here as a mass unit, and 1 ppm corresponds to 1 mg of coloring oxide based on 1 kg of glass or glass ceramic.
[0099] Nd 2 Oh 3
[0100] Nd 2 O 3The content may be 0% by weight or > 0% by weight.
[0101] In the transparent glass ceramic produced from the lithium aluminosilicate glass according to the invention, in a preferred embodiment, by adding 0.0001 wt. % to 0.3 wt. % Nd 2 O 3 Reduces the objectionable coloration originating from the Fe / Ti coloring complex. Below 0.005 wt.%, the decolorization effect is relatively low, so Nd 2 O 3 A particularly preferred lower limit is 0.005 wt. %, in particular 0.01 wt. %, very particularly 0.03 wt. %. Above 0.3 wt. %, the brightness is deteriorated in an undesirable manner by absorption of the Nd band in the visible region. Therefore, it is preferred to add up to 0.2 wt. % Nd 2 O 3 The preferred range is 0.0001 wt% to 0.2 wt%. Nd 2 O 3 A particularly preferred range is from 0.01% to 0.2% by weight.
[0102] CoO
[0103] Adding CoO in an amount of up to 30 ppm, preferably up to 20 ppm, can promote decolorization. CoO contents of 0.1 ppm to 20 ppm are preferred. Above 30 ppm, CoO in the transparent glass-ceramic produces a reddish hue.
[0104] In a preferred embodiment, the lithium aluminosilicate glass ceramic product according to the present invention has the following composition, which comprises in weight % based on oxides:
[0105] For the purpose of facilitating economically viable production, the lithium aluminosilicate glass ceramic product according to the invention has a particularly preferred composition, which comprises, based on the weight % of the oxides:
[0106] Clarifying agent
[0107] The glass ceramic article preferably contains at least one fining agent from the group of arsenic oxide and / or tin oxide, which is added for melting of the crystallizable glass of the glass ceramic article. Depending on the choice of the main fining agent, a distinction is made between two embodiments. When more than one fining agent is present, the main fining agent is the fining agent with the highest proportion in wt. %.
[0108] In the first embodiment, As2 O 3 Used as the main clarifier and in a glass ceramic product in an amount of 0.2 wt % to 2 wt %. The minimum content is required for sufficient clarification and is advantageous for high brightness and low coloring. Therefore, the minimum content is preferably 0.2 wt %, more preferably 0.4 wt %. Contents above 2 wt % are disadvantageous for the time / temperature durability of glass ceramics because the thermal expansion coefficient changes when higher temperatures are used. Since arsenic evaporates at melting temperatures, filtering measures are required and higher contents are also economically disadvantageous from an environmental perspective. The preferred upper limit is 1.5 wt %, more preferably 1.2 wt %. In this embodiment, SnO 2 The content is preferably less than 0.2% by weight because addition causes additional absorption and worsening of coloration.
[0109] MgO / As 2 O 3
[0110] When arsenic oxide is selected as the main clarifier, MgO / As 2 O 3 The ratio of the components is crucial to achieve a balance between low coloration and high brightness of the glass ceramic and good melting behavior and refinability of the glass. 2 O 3 The ratio of the components (in % by weight) is preferably less than 0.7, more preferably less than 0.5, and particularly preferably less than 0.45. As mentioned above, due to the higher As 2 O 3 The higher MgO content increases the formation of the coloring complex during this formation. Due to the preferred upper limit of the quotient of the two, the effects are added in an advantageous manner. The ratio of the components should preferably be greater than 0.05, more preferably greater than 0.1. The reason is that despite the relatively high As 2 O 3 content, but the melting temperature will still increase when the MgO content is lower.
[0111] In the second embodiment, for environmentally friendly clarification, SnO 2 It is used as the main fining agent and its content is preferably less than 0.3 wt. %, more preferably less than 0.10 wt. %, and particularly preferably less than 0.08 wt. %. Since absorbing Sn / Ti coloring species are formed in the crystallization, a higher content of this component is essential for the coloring of glass ceramics. SnO 2 A favorable lower limit is a minimum content of 0.04% by weight. In particular, when no fining agents arsenic oxide or antimony oxide are used, the polyvalent tin oxide counteracts bubble formation (reboiling) at the noble metal in the molten bath.
[0112] In this embodiment, the glass ceramic article or the crystallizable glass preferably has an environmentally friendly composition. This is understood to mean that the composition technically does not contain arsenic oxide and antimony oxide as conventional fining agents, meaning that the content of the two fining agents is preferably below 1000 ppm, further preferably below 500 ppm.
[0113] MgO×SnO 2
[0114] When choosing SnO 2 When used as the main clarifier, MgO×SnO 2 The compositional result is critical to reconcile low coloration and high brightness with good clarifyability, low melting and forming temperatures.
[0115] MgO×SnO of the glass according to the present invention 2 The result of the components (all in weight %) is preferably less than 0.06, more preferably less than 0.04, and particularly preferably less than 0.03. The reason for the upper limit of the result is that the MgO component increases the intensity of the Sn / Ti absorption band. For sufficient clarification and low melting and molding temperatures, the product of the components should be greater than 0.004, more preferably less than 0.008, and particularly preferably greater than 0.01.
[0116] This can be achieved by adding other chemical clarifiers (such as Sb 2 O 3 and cerium oxide) and clarification additives (such as sulfates or halides) help to 2 O 3 or SnO 2 For each component, the preferred upper limits listed should be noted. 2 O 3 , the total amount of clarifying additives is preferably less than 1 wt. %.
[0117] However, Sb 2 O 3 The component has an adverse effect on brightness and coloring. Therefore, the content is preferably limited to less than 0.2 wt %, more preferably less than 0.1 wt %. More preferably, no Sb is added. 2 O 3 And there is only a content of less than 100 ppm originating from impurities.
[0118] It is preferred to omit the addition of halides as fining aids. They evaporate during melting and enter the melting tank environment. There, corrosive compounds such as HF, HCl and HBr are formed, which are disadvantageous because they corrode refractory bricks in the melting tank and the exhaust gas duct. Therefore, the glass-ceramic product preferably does not contain F, Cl, Br, except for the unavoidable impurity content, and the content of each is preferably less than 500 ppm.
[0119] The above compositions are to be understood as such that the listed ingredients represent at least 98% by weight, typically 99% by weight of the total composition. Various elements, such as F, Cl, alkali metals Rb, Cs, rare earths or compounds of rare earth elements, such as Hf, are common impurities in batches of raw materials used on an industrial scale.
[0120] If an ingredient is specified as 0% by weight, this means that the ingredient in question was omitted from the raw material batch. However, these ingredients may be present as unavoidable impurities.
[0121] Depending on the choice of batch raw materials and the process conditions in the melt, the water content of the crystallizable glass used for producing the glass-ceramic article is preferably between 0.015 and 0.06 mol / l. This corresponds to 0.16 to 0.64 mm -1 Once converted into a glass ceramic, the IR band used to determine the water content changes. This changes the β-OH value of the glass ceramic without changing the water content. Methods for determining the β-OH value are described, for example, in EP 1074520A1.
[0122] The bubble quality of the crystallizable lithium aluminosilicate glass and / or the glass ceramic products produced therefrom meets the requirement that the bubble number is preferably less than 5 bubbles / kg, preferably less than 2 bubbles / kg. This applies to bubbles with a one-dimensional size greater than 0.1 mm. This is preferably ensured by the composition and component relationships of the invention and technical measures, such as the construction of the tank, energy input and tank production. In order to achieve particularly good bubble quality and high tank production, the crystallizable glass is optionally refined by a high-temperature refining operation at a temperature greater than 1750° C.
[0123] The glass-ceramic article has the same composition as crystallizable lithium aluminosilicate glass.
[0124] Crystallizable lithium aluminosilicate glass is transformed into glass-ceramic articles by a multi-stage heat treatment.
[0125] The transparent colorless glass-ceramic product according to the present invention contains high quartz mixed crystals as a main crystal phase.
[0126] The coloration (color c*) of the invention associated with the use of mineral lithium raw materials is greater than 3 to 7. The preferred upper limit is 6, more preferably 5, particularly preferably 4.5. In order to be able to use the highest content of mineral lithium raw materials in the melt for economically viable production, the preferred color c* is greater than 3.2, more preferably greater than 3.5.
[0127] The brightness Y of the glass ceramic article is preferably greater than 84%, more preferably greater than 85%, particularly preferably greater than 86%.
[0128] The values for coloration (chromaticity c*) and lightness Y apply to measurements carried out in accordance with standard DIN 5033 on polished specimens with a thickness of 4 mm with standard illuminant D65 at 2°.
[0129] In order to minimize scattering, it is advantageous to minimize the crystallite size. The average crystallite size is preferably less than 50nm. In order to realize a short ceramicization time less than 300min, the average crystallite size is preferably greater than 25nm. The crystalline phase content of the high quartz mixed crystal of the glass ceramic is preferably at least 50 wt % and preferably at most 80 wt %.
[0130] The scattering or haze is measured on a polished sample of a LAS glass ceramic with a thickness of 4 mm according to ASTM D1003-13. The haze value is preferably less than 2.5%, more preferably less than 2%, particularly preferably less than 1.5%. Above 2.5%, the haze is usually visually visible. As a result, the transparent glass ceramic according to the invention has no visually visible light scattering. Looking through the article, the bottom side coating is not deformed, and the bright display, such as a display or screen, below the glass ceramic plate is clearly seen with sharp outlines and without scattering.
[0131] The thermal expansion of the glass ceramic is preferably adjusted to about 0±0.5·10 -6 / The value of K.
[0132] The preferred geometry of the glass ceramic according to the invention or the articles produced therefrom is in the form of a sheet. The sheet preferably has a thickness of 2 mm to 20 mm, since this opens up important applications. Lower thicknesses weaken the strength; higher thicknesses are not economically feasible due to higher material requirements. Except for use as safety glass, where high strength is important, the thickness is therefore preferably selected to be no more than 6 mm.
[0133] Preferred products according to the invention are rolled glass-ceramic plates.
[0134] The maximum area size of the product in production is limited by the width of the belt in the thermoforming (rolling or float) and the size of the ceramizing furnace. For special applications, such as fire-resistant glass or kitchen countertops with integrated cooking area, dimensions with an edge length of up to 3 m are preferred, because in the case of windows this dimension reaches the height between the floors and the width of the cooking area in commercial kitchens.
[0135] Glass ceramic plate and preferably the product produced therefrom can be not only flat in shape, but also three-dimensionally formed. For example, folded, angled or curved plates can be used. Plates can be right angles or have other shapes, and flat areas include three-dimensionally formed areas, such as pots or platforms or areas introduced by rolling as peaks and valleys. In hot forming operations, for example, by structured forming rollers, or by downstream hot forming on the starting glass, such as by burners, infrared sources or laser radiation or by gravity reduction, the geometrical shaping of the plate is carried out. In the case of ceramicization, a supporting ceramic mold is used. These substrates can be three-dimensional shapes or flat, to adjust the geometry. If the application requires, one or both sides can be polished subsequently.
[0136] Production method of glass ceramic products
[0137] The method for producing a transparent, colorless lithium aluminosilicate glass-ceramic article according to the invention is characterized by the following steps: a) providing a batch formulation consisting of industrial raw materials, the industrial raw materials comprising powdered batch components and 20% to 80% by weight of ceramic fragments, the batch components comprising mineral lithium raw materials; b) melting the batch formulation and clarifying at a temperature above 1550°C; c) Cooling the glass melt and heating it to near the processing temperature V A The temperature of the molding; and d) cooling to room temperature in an expansion furnace, wherein undesirable stresses in the glass are removed; e) inspect, process and provide vitreous products; f) crystallizing the glass product in a ceramicizing furnace to obtain a glass ceramic product having high quartz mixed crystals as a main crystal phase according to the present invention.
[0138] The batch recipe is designed so that after melting, a glass having the composition and properties according to the invention is formed. In the method according to the invention, in order to introduce Li 2 O, using cheap mineral raw materials and replacing at least a portion of conventional lithium carbonate. Preference is given to selecting eucryptite, spodumene and / or petalite, alone or in combination, because they allow the composition according to the invention to be provided, especially in Fe 2 O 3 and MnO 2 In the selection of raw materials, choose the common Fe 2 O 3 、MnO 2 、Na 2 O.K 2The absence of O and CaO impurities ensures suppliers and deposits that meet the composition desired by the present invention. The use of these mineral raw materials also reduces the release of carbon dioxide into the environment compared to the use of carbonates.
[0139] With relatively high content of alkali Na 2 O.K 2 O, MgO or P 2 O 5 , B 2 O 3 Mineral lithium raw materials containing fluorine, such as lepidolite, lepidolite, hectorite and jadalite, may be disadvantageous. Therefore, lepidolite, lepidolite, hectorite and jadalite are preferably not used.
[0140] For inexpensive production, preferably at least 1 wt. % Li is introduced into the glass ceramic product via a mineral lithium feedstock. 2 More preferably, at least 1.2 wt. %, particularly preferably at least 1.4 wt. %, of Li O is introduced into the glass ceramic product via the mineral lithium raw material. 2 O content. Preferred lithium raw materials used alone or in combination are eucryptite, spodumene and / or petalite. Spodumene and / or petalite are preferred due to their economically viable availability.
[0141] By adding preferably 20 to 80% by weight of ceramic chips in the batch recipe, melting is improved and a higher pot yield is obtained. These ceramic chips usually come from the production of the same glass and are waste volumes of glass or glass ceramics obtained in quality control or cutting to size, which have been melted with the mineral lithium raw material and put back into production.
[0142] Melting and fining are carried out at a maximum temperature of more than 1550° C., preferably more than 1600° C. Optionally, a high-temperature fining unit is used, and the maximum temperature of the glass melt in the melting tank is higher than 1750° C., preferably higher than 1850° C. The use of electrical energy by the additional high-temperature fining operation enables the use of electrical energy generated in an environmentally friendly manner. Thus, the reduction of CO in the melting process can be better met. 2 requirements.
[0143] In the production of glass products, methods established in glass technology such as casting, pressing, blowing, rolling and float processes are used. It is preferred to produce a glass ribbon with a plate-like geometry by float or rolling, and to avoid stress, it is cooled to room temperature in an annealing furnace. After ensuring the quality with respect to volume and surface defects, a plate of the desired size is produced from the glass ribbon. The preferred forming method for the glass melt is the method using two rollers, because this method has an advantage due to faster cooling when the composition has a tendency to devitrification.
[0144] The next step is to ceramize the glass article on a flat or three-dimensional high temperature stable substrate (firing aid). Ceramics are preferably carried out in a roller furnace, which ensures the high heating rate desired on an industrial scale. In order to produce the desired microcrystalline structure, ceramization is carried out in a two-step process comprising nucleation and crystallization in a known manner.
[0145] The ceramicizing time is preferably less than 300 min, more preferably less than 200 min, particularly preferably less than 150 min.
[0146] Application of glass ceramic products
[0147] The transparent lithium aluminosilicate glass-ceramic articles are preferably used as fire protection glass, furnace viewing windows, oven viewing windows (which can be used in particular for pyrolysis furnaces), cooking surfaces (which may have a bottom side coating), covers in the field of lighting, safety glass (which is preferably used for laminated composites), or carrier plates or oven linings (which are preferably used for heat treatments).
[0148] In the case of oven viewing windows, good transparency of the combustion space and the flames is desirable. In the case of cooking surfaces with a colored bottom coating, the color of the bottom coating is not distorted by the color of the glass ceramic. For the uses mentioned, high values of the brightness Y and low chromaticity c* in combination with low, imperceptible light scattering are preferred according to the invention.
[0149] By applying an opaque coating on the top and / or bottom, a colored cooking surface can be produced with the desired visual cover and prevents the technical equipment under the cooking surface from being seen. The cooking surface is heated as usual by a gas burner or a radiant heater or induction.
[0150] The openings in the coating allow sensor areas, color and white display devices and displays to be installed. The display devices consist of light-emitting electronic components, such as light-emitting diodes, OLEDs, LCDs or fluorescent displays.
[0151] A further preferred use of the glass ceramic article is as a carrier plate or oven lining. In the ceramic, solar or pharmaceutical industries or in medical technology, it is particularly suitable for production processes under ultra-clean conditions, as an oven lining for chemical or physical coating methods, or as a chemically resistant laboratory finish. It is also used for high or very low temperature applications, as a furnace window for combustion furnaces, as a heat shield for shielding against hot environments, as a cover for reflectors, searchlights, projectors or copiers; for applications under thermomechanical stress, for example in night vision equipment or as a cover for heating elements, in particular as a cooking, grilling or frying surface, as a white object, as a heat source cover, as a wafer substrate, as an object with UV protection, as a panel for electronic devices and / or IT devices, such as mobile phones, laptops, scanner panels or as a material for accommodating components, or as a bulletproof component. DETAILED DESCRIPTION
[0152] The present invention is illustrated by the following examples.
[0153] A crystallizable glass for producing glass-ceramic articles from a batch of raw materials customary in the glass industry was melted at a temperature of 1620° C. for 4 hours.
[0154] The raw materials in the selected batches are: lithium carbonate, spodumene, eucryptite, petalite, aluminum oxide, aluminum hydroxide, aluminum metaphosphate, quartz sand, sodium nitrate and saltpeter, sodium carbonate and potassium carbonate, magnesium oxide, lime, dolomite, strontium carbonate, barium carbonate, zinc oxide, arsenic oxide or another arsenic compound, titanium oxide, zirconium silicate, zirconium oxide, neodymium oxide, and optionally tin oxide.
[0155] After melting the batch in a sintered silicate glass crucible, the laboratory melt was poured into a Pt / Rh crucible with an inner quartz glass crucible and homogenized by stirring for 60 min at a temperature of 1600° C. After homogenization, the glass was refined at 1640° C. for 3 hours.
[0156] Then, the casting size is about 120×140×30mm 3 The blocks were cut into pieces and cooled to room temperature in an annealing furnace starting at 660°C to relieve stress. The castings were divided into the sizes required for research and ceramicization.
[0157] Table 1 shows the composition and component relationships of the crystallizable glass and glass-ceramic products of the present invention and comparative glass-ceramic products produced therefrom. Also shown are the Li introduced via spodumene (S) and petalite (P). 2 O content. Total content (C=Li 2The insufficient amount in O ("total")-S-P) is provided by lithium carbonate and is not reported in the table. Compositions 1 to 8 are those in the context of the present invention, while compositions 9 to 12 are comparative glasses. The compositions are not added to exactly 100 wt.% due to impurities common in the industrial batches of raw materials used. Common impurities are F, Cl, B, Rb, Cs, Hf, which are usually less than 0.2 wt.%, even if they are not deliberately introduced into the composition. They are usually entrained by the raw materials used for the components, for example, Rb and Cs by Na and K raw materials, or Hf by Zr raw materials.
[0158] For some glass compositions, the CoO and Cr components that are unfavorable to the chromaticity c* are analyzed. 2 O 3 The detection limit of the laser ablation-inductively coupled plasma mass spectrometry (LA-ICP-MS) used for the determination of the content of NiO components was at least 1 ppm.
[0159] Table 2 shows the properties of transparent glass ceramic products having high quartz mixed crystals as the main crystalline phase produced by a detailed ceramization procedure. Examples 1-14 are examples, and Examples 15-18 are comparative examples.
[0160] Table 2 gives the optical properties of the glass-ceramic products, in particular the spectral transmittance at 400 nm [%], the infrared transmittance at 1600 nm [%], the brightness Y of the CIE color system and the brightness L* of the CIELAB system and the color coordinates a*, b*, the parameter c* as a measure of the color (chromaticity), and the haze value as a measure of the scattering. For the selected glass-ceramic products, the thermal expansion between 20 and 700 ° C [10 -6 / K].
[0161] Comparative Examples 15-17 were produced neither from spodumene nor from petalite, but only from lithium carbonate as a lithium source, thus achieving low Fe 2 O 3 and MnO 2 However, the values of brightness Y and color (chromaticity c*) are only slightly better than those of the glass ceramic product examples according to the invention. Therefore, these compositions not according to the invention are disadvantageous in terms of meltability and raw material costs.
[0162] Comparative Example 18 is produced from glass composition 12 using petalite as raw material and has Fe 2 O 3 and MnO 2 content, but due to the unfavorable range of composition and ingredient relationship, there are disadvantages in brightness, color and spectral transmittance values at 400 and 1600nm.
[0163] Ceramics are carried out in a laboratory oven that allows high heating rates. To produce glass ceramic articles, two ceramizing programs with different rates are used. For the same crystallizable glass, the slower program 1 generally achieves lower scattering, but the color values are then poorer.
[0164] Ceramicization procedure 1 (ceramicization time 156min): a) Rapidly heated from room temperature to 720°C within 24 minutes, b) Raise the temperature from 720°C to 800°C within 40 min (heating rate 2°C / min), c) the temperature was increased from 800°C to 890°C within 53 min (heating rate 1.7°C / min), d) Maintain the maximum temperature of 890°C for 10 minutes, e) Cool from 890°C to 600°C in 29 min (10°C / min), and then quickly cool to room temperature.
[0165] Ceramicization procedure 2 (ceramicization time 89 minutes): a) Rapidly heated from room temperature to 715°C within 24 minutes, b) Raise the temperature from 715°C to 800°C in 19 min (heating rate 4.5°C / min), c) the temperature was increased from 800°C to 885°C in 27 min, the temperature was heated from 800°C to 819°C in 18 min (heating rate 1.1°C / min), and further heated to 885°C at a rate of 8°C / min in 9 min (heating rate 7.3°C / min), d) the temperature was further increased from 885°C to 895°C within 6 min (heating rate 1.7°C / min), and the maximum temperature of 895°C was maintained for 4 min, e) Cool to 800°C within 9 min (10.6°C / min), and then quickly cool to room temperature.
[0166] The transmittance measurements were performed on polished plates with a thickness of 4 mm using a Perkin-Elmer Lambda 900 instrument with a D65 standard illuminant at 2°. The spectral values measured in the range of 380 nm to 780 nm, which represents the visible light spectrum, were used to calculate the brightness Y according to DIN 5033 for the selected D65 illuminant and a 2° observation angle. These measurements were also used to calculate the brightness L* and the color coordinates a*, b* and the chromaticity c* of the CIELAB system.
[0167] The scattering of the glass ceramic is determined by measuring the haze. The haze is measured here with illuminant C on panels with a thickness of 4 mm which are polished on both sides using the commercially available "Haze-guard plus" measuring instrument from BYK-Gardner in accordance with standard ASTM D1003-13 and characterized by the haze value.
[0168] Table 1: Glass composition for glass ceramic products according to the present invention Table 1 (continued)
[0169] Table 2: Ceramics conditions and properties of glass ceramic products according to the present invention Table 2 (continued) Table 2 (continued)
Claims
1. A transparent, colorless lithium aluminum silicate glass ceramic product having high quartz mixed crystal as the main crystal phase, characterized in that: In % by weight based on oxides, it essentially comprises the following components: Li2O 3-<4 Al2O3 19-24 SiO2 62-70 Na2O 0-1.5 K2O 0-1.5 MgO 0.01-<0.5 CaO 0-1.5 SrO 0-1.5 BaO 0-3 ZnO 0-3 TiO2>1.6-2.8 ZrO2 1-<2.5 P2O5 0-<4 Fe2O3 0.025-0.065 MnO2 0.002-0.05, and contains at least one fining agent selected from the group consisting of As2O3 and / or SnO2, in an amount up to 2% by weight. The chromaticity c* of the glass ceramic product is greater than 3 to 7 when measured at 2° with a D65 standard light source at a thickness of 4 mm.
2. The lithium aluminum silicate glass ceramic product according to claim 1, characterized in that: The following conditions apply: 0.2 wt%≤Na2O+K2O≤1.5 wt%.
3. The lithium aluminosilicate glass ceramic product according to any one of claims 1 and 2, characterized in that It contains MgO in an amount of 0.05 to 0.4 wt %.
4. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that The following conditions apply: 0.1 wt%≤CaO+SrO≤1 wt%.
5. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that It contains P2O5 in an amount of 0.01 wt% to less than 1.3 wt%.
6. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that It contains Fe2O3 in an amount of 0.03 wt% to 0.055 wt%.
7. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that It contains MnO2 in an amount exceeding 0.01 wt%.
8. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that It contains Cr2O3 and / or NiO, wherein the sum of the Cr2O3+NiO contents is less than 7 ppm.
9. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that It contains Nd2O3, wherein the Nd2O3 content is 0.0001% to 0.2% by weight, preferably 0.01% to 0.2% by weight.
10. The lithium aluminosilicate glass ceramic product according to claim 1, characterized in that: In % by weight based on oxides, it comprises the following components: Li2O 3.4-<4.3 Al2O3 20-24 SiO2 62-68 Na2O 0.05-1 K2O 0-1 Na2O+K2O 0.2-1.2 MgO 0.1-0.4 CaO 0.05-0.8 SrO 0-1 CaO+SrO 0.1-1.2 BaO 0-2 ZnO>0-2.5 TiO2>2-2.8 ZrO2 1-<2.2 P2O5 0-1.5 Fe2O3 0.03-0.065 MnO2 0.005-0.
03.
11. The lithium aluminum silicate glass ceramic product according to claim 1, characterized in that: In % by weight based on oxides, it comprises the following components: Li2O 3.4-<4 Al2O3 20-23 SiO2 62-68 Na2O 0.05-0.9 K2O 0.05-0.9 Na2O+K2O>0.4-<1 MgO 0.1-0.4 CaO 0.05-<0.6 SrO 0.02-1 CaO+SrO 0.1-0.8 BaO 0-2 ZnO 0.5-2.5 TiO2>2-2.8 ZrO2 1-<2.2 P2O5 0.01-<1 Fe2O3 0.03-0.055 MnO2>0.01-0.
03.
12. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that It contains As2O3 as a primary fining agent in an amount of 0.2 to 2 wt%; Preferably, the ratio of the components MgO and As2O3 is subject to the following conditions: MgO / As2O3<0.
7.
13. The lithium aluminosilicate glass ceramic product according to any one of the preceding claims 1 to 11, characterized in that It contains SnO2 as a main fining agent in an amount of 0.04 to 0.3 wt%; Preferably, the product of the components MgO and SnO2 is subject to the following conditions: 0.004 <MgO×SnO2<0.6。 14. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that For a thickness of 4 mm, it has a brightness Y greater than 84% and / or a haze value less than 2.5%.
15. The lithium aluminosilicate glass-ceramic product according to any one of the preceding claims, characterized in that It is in the form of a plate having a thickness of 2 mm to 20 mm.
16. A method for producing a transparent, colorless lithium aluminosilicate glass-ceramic article according to any one of claims 1 to 15, It is characterized by the following steps: a) providing a batch formulation consisting of industrial raw materials, the industrial raw materials comprising powdered batch components and 20% to 80% by weight of ceramic fragments, the batch components comprising mineral lithium raw materials; b) melting the batch formulation and clarifying at a temperature above 1550° C.; c) Cooling the glass melt and heating it to near the processing temperature V A Temperature molding; and d) cooling to room temperature in an expansion furnace, wherein undesirable stresses in the glass are removed; e) inspect, process and provide vitreous products; f) crystallizing the glass product in a ceramicizing furnace to obtain a glass ceramic product having high quartz mixed crystals as a main crystal phase.
17. The method for producing a lithium aluminosilicate glass ceramic product according to claim 16, characterized in that Spodumene and / or petalite are used as mineral lithium raw materials and a Li2O content of at least 1% by weight is introduced into the glass ceramic article.
18. Use of the glass ceramic plate according to claim 15 as fire protection glass, furnace window, oven window, cooking surface, lighting field cover, safety glass, carrier plate or furnace lining.
Citation Information
Patent Citations
Li2O-Al2O3-SiO2 crystallized glass and crystallizable glass therefor
EP1074520A1
Lithium-aluminium-silicate glass with short ceramisation time
EP1837312A1
Li2O-Al2O3-SiO2-BASED CRYSTALLIZED GLASS
WO2007139068A1
Transparent, colorless low-titania beta-quartz glass-ceramic material
WO2008065166A1
Transparent, colorless titania-free beta-quartz glass-ceramic material
WO2008065167A1